If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -3 = 2x Reorder the terms: -3 + 3x = 2x Solving -3 + 3x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -3 + 3x + -2x = 2x + -2x Combine like terms: 3x + -2x = 1x -3 + 1x = 2x + -2x Combine like terms: 2x + -2x = 0 -3 + 1x = 0 Add '3' to each side of the equation. -3 + 3 + 1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 1x = 0 + 3 1x = 0 + 3 Combine like terms: 0 + 3 = 3 1x = 3 Divide each side by '1'. x = 3 Simplifying x = 3
| 6.4x-4.9x=-45 | | 5c^3=20c | | 9-5n+1=15 | | 4c+3-2c+7= | | 5x+6=4x+2 | | F=24l | | 4x+25=12x-55 | | (0)+3y=12 | | V^2+7v-18= | | 12x-29=7x+1 | | 8(3n+5)=-32 | | b+b+b+b= | | x+(x+1)+(x+2)=222 | | 3a+3b= | | 3b+3b= | | 9x-4y=-11 | | 3a+8a= | | 9n-28=53 | | -2(-5)(-10)= | | 2(x+5)=3(x-10) | | 22-5x=-28 | | 3x^2+2x-30=0 | | (-5)(10)= | | y+-4=-15 | | 3X^2+10X=-2 | | 9= | | 4a*9a= | | 96=2(6+2x)+2(x) | | (-12)+(-23)= | | (x^2+13)=225 | | 10=x+8 | | 32-12t+t^2= |